Socio-educational interventions with non-incarcerated, adjudicated youth in Rio Grande do Sul: a brazilian experience. - Craidy, Carmen Maria (Facultad de Trabajo Social y Desarrollo Humano, 2009)
This article describes an innovative intervention for troubled juveniles who have been adjuducated for criminal offenses but who have not been incacerated. It begins by outlining the legislation that legitimizes and supports the intervention, follows by detailing the intervnetion itself, and concludes by offering a summary of outcomes experienced by the program’s participants. As a university/communtiy partnership the intervention has shown positive results in Brazil, and offers promise as an effective program throughout the Americas.